A kind of thermoplastic resin coating and its preparation method and application
Through the combination of thermoplastic acrylic resin, modified epoxy resin and modified filler, the problem of insufficient adhesion, aging resistance and waterproof performance of glassware coatings is solved, and better waterproof, alkali resistance and corrosion resistance are achieved. It improves the performance of glassware and the application prospects of coatings.
Patent Information
- Application Number
- CN202411406587.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-10
AI Technical Summary
During use, existing glassware coatings have problems such as insufficient adhesion, aging resistance, waterproofing and acid and alkali resistance, which limits their application environment and fields.
Using a combination of thermoplastic acrylic resin, modified epoxy resin and modified filler, a dense three-dimensional network is formed by introducing flexible linkages and multi-group particles, which enhances the intermolecular force and reduces the number of free groups and water molecules. , improve the waterproof, aging resistance and corrosion resistance of the coating.
While maintaining excellent brightness and wear resistance, the waterproof, alkali resistance, aging resistance and corrosion resistance of the paint are significantly improved, meeting the surface coating performance needs of glassware products, and expanding the application prospects of paint.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a thermoplastic resin coating and a preparation method and application thereof. Background Art
[0002] In recent years, with the improvement of people's living standards and changes in aesthetic concepts, the decoration technology of glassware has developed rapidly, which has triggered consumers' desire to decorate glassware. Therefore, in order to meet the market demand for high-quality and personalized glass decorations, coatings for decorating glassware have emerged. In addition to the basic decorative function, glassware decorative coatings usually have heat insulation, protection, UV resistance and wear resistance, which are used to improve the performance of glassware.
[0003] In recent years, with the increasing awareness of environmental protection, more and more research has been devoted to the development of non-toxic, low VOC (volatile organic compound) emission glassware coatings. In order to improve the smoothness, brightness and wear resistance of the coatings, R&D personnel have also continuously improved the formula of glassware coatings, and introduced thermoplastic resin raw materials to enhance the various properties of the original coatings. However, at the same time, with the change of formula, glassware coatings have gradually encountered various problems in the use process, such as insufficient adhesion, aging resistance, waterproof, acid and alkali resistance, and corrosion resistance, which have limited the application environment and field of glassware coatings.
[0004] Therefore, in order to better solve the above problems, the present application provides a thermoplastic resin coating and a preparation method thereof, which can maintain excellent brightness and wear resistance while having good coating waterproofing, alkali resistance, aging resistance and corrosion resistance, meeting the performance requirements of various existing glassware products for surface coatings, thereby making the glassware have better performance, and the coating can also have excellent application prospects. Summary of the invention
[0005] The first aspect of the present application provides a thermoplastic resin coating as mentioned above, wherein the raw materials are, in parts by mass: 20 to 40 parts of thermoplastic acrylic resin, 10 to 20 parts of fatty alcohol, 10 to 15 parts of modified epoxy resin, 40 to 60 parts of glass frit, 4 to 8 parts of pigment filler, 10 to 20 parts of modified filler, 0.2 to 0.8 parts of mildewproofing agent, 1.5 to 3 parts of defoaming agent, and 100 to 200 parts of solvent.
[0006] As a preferred solution, the mass ratio of the thermoplastic acrylic resin, the fatty alcohol and the modified epoxy resin is 25-35:14-18:12-15.
[0007] As a preferred solution, the mass ratio of the thermoplastic acrylic resin, the fatty alcohol and the modified epoxy resin is 28-32:15-16:13-14.
[0008] As a preferred solution, the mass ratio of the thermoplastic acrylic resin, the glass frit and the modified filler is 25-35:50-55:13-18.
[0009] As a preferred solution, the mass ratio of the thermoplastic acrylic resin, the glass frit and the modified filler is 28-32:51-53:14-16.
[0010] As a preferred solution, the viscosity of the thermoplastic acrylic resin is 5000-10000 mPa·s at 25°C.
[0011] As a preferred solution, the viscosity of the thermoplastic acrylic resin is 7000-8500 mPa·s at 25°C.
[0012] As a preferred solution, the fatty alcohol is a combination of hexadecanol and dodecanol.
[0013] As a preferred solution, the mass ratio of hexadecanol to dodecanol is 4.5-5:1.2-1.5.
[0014] As a preferred solution, the preparation method of the modified epoxy resin comprises the following steps: S1: bisphenol A epoxy resin and trimethylolpropane triglycidyl ether are mixed and added to a reaction container, and stirred at 60-80 rpm for 50-55 min, and then toluene diisocyanate and 2-ethyl-4-methylimidazole are added in sequence, and stirred at 80-100 rpm for 20-30 min each time, and after stirring, nitrogen is used to replace the air atmosphere to protect the reaction container; S2: firstly heat the temperature to 70- 80℃, keep warm for 3~3.5h, then raise the temperature to 110~115℃, and keep warm for 2~2.5h to obtain the pre-product; S3: finally, mix the pre-product, glutaric anhydride, maleic anhydride and vinyl triethoxysilane and add deionized water, then transfer into a sealed reactor and control the reactor pressure to 0.8~1MPa, then raise the temperature to 120~140℃, keep warm for 4~5h, and naturally cool to room temperature after the reaction is completed. The product is obtained by cyclic washing with methanol and ethanol and drying.
[0015] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, trimethylolpropane triglycidyl ether, toluene diisocyanate and 2-ethyl-4-methylimidazole is 11-13: 4-4.5: 1.5-2: 0.05-0.1.
[0016] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 180-220 g / eq; the viscosity of the bisphenol A epoxy resin is 12000-18000 mPa·s at 25°C.
[0017] As a preferred solution, the mass ratio of the pre-product, glutaric anhydride, maleic anhydride and vinyl triethoxysilane is 10-12: 1-1.2: 1.4-1.8: 0.2-0.22.
[0018] The modified epoxy resin added in this application can help improve the overall waterproof, aging and corrosion resistance of the coating. The added modified epoxy resin can not only enhance the toughness of the overall molecular chain of the coating system by introducing flexible segments, but also enhance the entanglement efficiency of the molecular chain network inside the system, thereby forming a more compact three-dimensional network, enhancing the intermolecular force, reducing the number of free groups and free molecules (including water molecules), and limiting their activity space inside the system, helping to improve the waterproof, aging and corrosion resistance of the coating; on the other hand, the added modified epoxy resin can form a good interaction force with the multiple groups on the surface of the modified filler particles, thereby enhancing the connection between them, reducing the pore size of the pores formed by the filler particles in the system, thereby avoiding the negative impact of the large particle pore size on waterproof penetration, mechanical connection and support, and maintaining the fixity of the filler particles in the system to avoid the influence of agglomeration and segregation on the comprehensive performance.
[0019] As a preferred solution, the glass frit is at least one of a silicate glass frit, a borate glass frit and an aluminate glass frit.
[0020] As a preferred solution, the glass frit is a silicate glass frit.
[0021] As a preferred solution, the pigment filler is at least one of iron oxide red, cobalt blue, manganese violet and lead molybdate.
[0022] As a preferred scheme, the preparation method of the modified filler includes the following steps: S1: adding copper sulfate pentahydrate and titanium dioxide to a DMF solution, heating to 65-75°C, adding succinic anhydride and γ-aminopropyltriethoxysilane, and stirring at 60-80rpm for 40-50min; S2: adding a mixed DMF solution of 1,3,5-benzenetricarboxylic acid and 1,4-diaminobenzene, heating to 80-85°C, stirring at 60-80rpm for 60-90min until uniform, then cooling to 45-50°C, stirring at 30-40rpm, and keeping warm for 16-20h; S3: after the reaction is completed, naturally cool to room temperature, stand for 4-6h, then centrifuge and filter, wash with DMF and deionized water 2-3 times in turn, and vacuum dry until completely dry.
[0023] As a preferred solution, the mass ratio of copper sulfate pentahydrate, titanium dioxide, succinic anhydride and γ-aminopropyltriethoxysilane is 3.4-3.6:0.6-0.8:1.4-1.8:0.3-0.35.
[0024] As a preferred solution, the average particle size of the titanium dioxide is 10-15 nm.
[0025] As a preferred solution, the mass ratio of the copper sulfate pentahydrate, 1,3,5-benzenetricarboxylic acid and 1,4-diaminobenzene is 3.4-3.6:2.2-2.4:1.2-1.4.
[0026] In this application, the addition of the above-mentioned modified filler can effectively improve the waterproof, corrosion-resistant, alkali-resistant and heat-resistant properties of the resin coating in glassware applications. The modified filler can use the middle framework particles as the adsorption center, and through the guiding effect of the multi-group particles embedded on the surface, effectively absorb the internal trace water molecules after the coating is cured, thereby cutting off the continuous connection of the water molecules inside the coating, thereby greatly enhancing the resistance of water molecules from the external surface to the inside under the premise of removing internal moisture, and the framework particles can maintain a good water molecule storage effect at the use temperature of most glassware, and still remain non-desorbed at long-term high ambient temperatures, and greatly improve the mechanical and heat-resistant properties of the coating through the mechanical support of the frame structure and its own thermal stability structure; on the other hand, the added three-dimensional structure can greatly increase the steric hindrance between the organic molecules of the internal coating system, thereby reducing the effect and reaction probability between free molecules, thereby reducing internal reactions, and reducing the collision probability of active groups, so as to have long-term aging resistance, and have good resistance to corrosion molecules with water molecules as carriers.
[0027] As a preferred solution, the mildew inhibitor is at least one of isothiazolinone, quaternary ammonium salt, benzimidazole or triazine compounds.
[0028] As a preferred solution, the mildew inhibitor is 1,2-benzisothiazolin-3-one.
[0029] As a preferred solution, the defoaming agent is at least one of silicone defoaming agents.
[0030] The second aspect of the present application provides a method for preparing the above-mentioned thermoplastic resin coating, which specifically includes the following steps: S1: adding a thermoplastic acrylic resin, a fatty alcohol, a modified epoxy resin, a pigment filler and a modified filler to a solvent, heating to 60-70°C and stirring for 1.5-2h until uniform; S2: grinding the glass frit into fine powder of suitable particle size and adding it to a mixture with an antifungal agent and a defoamer, then mixing in a high-speed mixer at a speed of 600-800rpm for 40-50min, then taking it out and letting it stand for vacuum defoaming for 15-20min, and obtaining the coating after completion.
[0031] As a preferred solution, the average particle size of the fine powder of the glass frit is 1.5-2.5 µm.
[0032] The third aspect of the present application provides an application of the above-mentioned thermoplastic resin coating in glassware waterproof coating, glassware decorative coating, glassware sealing coating, and glassware antistatic coating.
[0033] The beneficial effects of this application are:
[0034] 1. A thermoplastic resin coating provided in the present application can maintain excellent brightness and wear resistance while having good coating waterproofing, alkali resistance, aging resistance and corrosion resistance, meeting the performance requirements of various existing glassware products for surface coatings, thereby making the glassware have better performance, and the coating can also have excellent application prospects.
[0035] 2. A thermoplastic resin coating provided in the present application, the addition of modified fillers can effectively improve the waterproof, corrosion-resistant, alkali-resistant and heat-resistant properties of the resin coating in glassware applications; the modified filler can use the middle framework particles as the adsorption center, and through the guiding effect of the multi-group particles embedded on the surface, effectively absorb the internal trace water molecules after the coating is cured, thereby cutting off the continuous connection of the water molecules inside the coating, thereby greatly enhancing the resistance of water molecules to penetrate from the external surface to the inside while removing the internal moisture, and the frame particles can maintain a good water molecule storage effect at the operating temperature of most glassware, and still remain non-desorbed under long-term high ambient temperatures, and greatly improve the mechanical and heat-resistant properties of the coating through the mechanical support of the frame structure and its own thermally stable structure.
[0036] 3. A thermoplastic resin coating provided in the present application, in which the added modified epoxy resin can not only enhance the toughness of the overall molecular chain of the coating system by introducing flexible segments, but also enhance the entanglement efficiency of the molecular chain network within the system, thereby forming a denser three-dimensional network, enhancing the intermolecular force, reducing the number of free groups and free molecules (including water molecules), and limiting their activity space within the system, helping to improve the waterproof, aging and corrosion resistance and other properties of the coating; on the other hand, the added modified epoxy resin can form a good interaction force with the multiple groups on the surface of the modified filler particles, thereby enhancing the connection between them, reducing the pore size of the pores formed by the filler particles in the system, thereby avoiding the negative impact of the large particle pore size on waterproof penetration, mechanical connection and support, and maintaining the fixity of the filler particles in the system to avoid the influence of agglomeration and segregation on the comprehensive performance. DETAILED DESCRIPTION
[0037] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0038] Example 1
[0039] Example 1 The first aspect provides a thermoplastic resin coating, the raw materials of which, in parts by mass, are: 30.5 parts of thermoplastic acrylic resin, 15.2 parts of fatty alcohol, 13.5 parts of modified epoxy resin, 52.5 parts of glass frit, 6 parts of color filler, 14.8 parts of modified filler, 0.5 parts of mildewproof agent, 1.8 parts of defoaming agent, and 120 parts of solvent.
[0040] The viscosity of the thermoplastic acrylic resin is 8200 mPa·s at 25° C. The thermoplastic acrylic resin product of model CFP7250 was purchased from Shandong Kafula Polymer Materials Co., Ltd.
[0041] The fatty alcohol is a composition of hexadecanol and dodecanol, and the mass ratio of the two is 4.8:1.4.
[0042] The preparation method of the modified epoxy resin comprises the following steps, calculated by mass: S1: 12.2 parts of bisphenol A epoxy resin and 4.4 parts of trimethylolpropane triglycidyl ether are mixed and added to a reaction container, and stirred at 80 rpm for 52 minutes, and then 2 parts of toluene diisocyanate and 0.08 parts of 2-ethyl-4-methylimidazole are added in sequence, and each addition is stirred at 100 rpm for 25 minutes. After the stirring is completed, the air atmosphere of the reaction container is replaced by nitrogen to protect the reaction container; S2: First, the temperature is raised to 80°C, and the mixture is kept at 80°C. The reaction was continued at a temperature of 3.2 hours, and then the temperature was raised to 110°C, and the reaction was continued at a temperature of 2.4 hours to obtain a pre-product; S3: Finally, 10.4 parts of the pre-product, 1.1 parts of glutaric anhydride, 1.6 parts of maleic anhydride and 0.21 parts of vinyltriethoxysilane were mixed and 240 parts of deionized water were added. Then, the mixture was transferred into a sealed reactor and the reactor pressure was controlled to 0.9 MPa. The temperature was raised to 130°C and the reaction was continued at a temperature of 5 hours. After the reaction was completed, the mixture naturally cooled to room temperature. The product was obtained by washing with methanol and ethanol in a cycle and drying.
[0043] The epoxy equivalent of bisphenol A epoxy resin is 200 g / eq, the viscosity of bisphenol A epoxy resin is 15000 mPa·s, and the temperature is 25° C. The E-44 product was purchased from Baling Petrochemical.
[0044] The glass frit is silicate glass frit purchased from
[0045] The pigment and filler is red iron oxide with an average particle size of 0.4µm.
[0046] The preparation method of the modified filler includes the following steps, calculated by mass: S1: 3.5 parts of copper sulfate pentahydrate and 0.7 parts of titanium dioxide are mixed and added to 120 parts of DMF solution, and after heating to 70°C, 1.6 parts of succinic anhydride and 0.32 parts of γ-aminopropyltriethoxysilane are added, and stirred at 80rpm for 45min; S2: 2.3 parts of 1,3,5-benzenetricarboxylic acid and 1.4 parts of 1,4-diaminobenzene mixed DMF solution (a total of 80 parts) are added, the temperature is increased to 82°C, and stirred at 80rpm for 90min until uniform, and then the temperature is reduced to 45°C, stirring at 40rpm and keeping warm for 18h; S3: after the reaction is completed, the temperature is naturally reduced to room temperature, and it is allowed to stand for 5.5h, and then centrifugally filtered, washed with DMF and deionized water three times in turn, and vacuum dried until completely dry.
[0047] The average particle size of titanium dioxide is 12 nm.
[0048] The mildew preventer is 1,2-benzisothiazolin-3-one; the defoamer is BYK-033N.
[0049] The second aspect of the present embodiment provides a method for preparing the above-mentioned thermoplastic resin coating, which specifically includes the following steps: S1: adding a mixture of thermoplastic acrylic resin, fatty alcohol, modified epoxy resin, pigments and modified fillers to a solvent, heating to 60-70°C and stirring for 1.5-2h until uniform; S2: grinding the glass frit into fine powder of suitable particle size and adding the mixture to a mixture with an antifungal agent and a defoaming agent, and then mixing the mixture in a high-speed mixer at a speed of 600-800rpm for 40-50min, and then taking out and standing for vacuum defoaming for 15-20min, and obtaining the coating after completion.
[0050] The average particle size of the fine powder of the glass frit is 2.2µm.
[0051] Example 2
[0052] The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the thermoplastic resin coating, in parts by mass, are: 25.2 parts of thermoplastic acrylic resin, 18 parts of fatty alcohol, 15 parts of modified epoxy resin, 55 parts of glass frit, 6 parts of pigment filler, 13.2 parts of modified filler, 0.5 parts of mildew inhibitor, 1.8 parts of defoamer, and 120 parts of solvent.
[0053] The fatty alcohol is a composition of hexadecanol and dodecanol, and the mass ratio of the two is 4.6:1.5.
[0054] Example 3
[0055] The specific implementation method of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the thermoplastic resin coating, in parts by mass, are: 34.8 parts of thermoplastic acrylic resin, 14 parts of fatty alcohol, 12 parts of modified epoxy resin, 50 parts of glass frit, 6 parts of pigment filler, 18 parts of modified filler, 0.5 parts of mildew inhibitor, 1.8 parts of defoamer, and 120 parts of solvent.
[0056] The fatty alcohol is a composition of hexadecanol and dodecanol, and the mass ratio of the two is 5:1.2.
[0057] Comparative Example 1
[0058] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the thermoplastic resin coating, in parts by mass, are: 22.8 parts of thermoplastic acrylic resin, 20.5 parts of fatty alcohol, 18.6 parts of modified epoxy resin, 52.5 parts of glass frit, 6 parts of pigment filler, 8.2 parts of modified filler, 0.5 parts of mildew inhibitor, 1.8 parts of defoamer, and 120 parts of solvent.
[0059] Comparative Example 2
[0060] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the thermoplastic resin coating, in parts by mass, are: 40.5 parts of thermoplastic acrylic resin, 15.2 parts of fatty alcohol, 8.5 parts of modified epoxy resin, 52.5 parts of glass frit, 6 parts of pigment filler, 20.5 parts of modified filler, 0.5 parts of mildew inhibitor, 1.8 parts of defoamer, and 120 parts of solvent.
[0061] Comparative Example 3
[0062] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified epoxy resin comprises the following steps, calculated by mass: S1: 18.8 parts of bisphenol A epoxy resin and 2.1 parts of trimethylolpropane triglycidyl ether are mixed and added to a reaction container, stirred at 80 rpm for 52 minutes, and then 0.8 parts of toluene diisocyanate and 0.01 parts of 2-ethyl-4-methylimidazole are added in sequence, and stirred at 100 rpm for 25 minutes each time. After stirring, nitrogen replaces the air atmosphere to protect the reaction container. device; S2: firstly heat to 80°C and keep warm for 3.2h, then heat to 110°C and keep warm for 2.4h to obtain a pre-product; S3: finally, 10.4 parts of the pre-product, 1.1 parts of glutaric anhydride, 1.6 parts of maleic anhydride and 0.21 parts of vinyltriethoxysilane are mixed and 240 parts of deionized water are added, then transferred into a sealed reactor and the reactor pressure is controlled to 0.9MPa, and then heated to 130°C and kept warm for 5h. After the reaction is completed, it naturally cools to room temperature, and the product is obtained after cyclic washing with methanol and ethanol and drying.
[0063] Comparative Example 4
[0064] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified epoxy resin comprises the following steps, calculated by mass: S1: 12.2 parts of bisphenol A epoxy resin and 4.4 parts of trimethylolpropane triglycidyl ether are mixed and added to a reaction container, stirred at 80 rpm for 52 minutes, and then 2 parts of toluene diisocyanate and 0.08 parts of 2-ethyl-4-methylimidazole are added in sequence, and stirred at 100 rpm for 25 minutes each time. After stirring, nitrogen replaces the air atmosphere to protect the reaction container. device; S2: firstly heat to 80°C and keep warm for 3.2h, then heat to 110°C and keep warm for 2.4h to obtain a pre-product; S3: finally, 20.5 parts of the pre-product, 0.6 parts of glutaric anhydride, 1.2 parts of maleic anhydride and 0.1 parts of vinyltriethoxysilane are mixed and 240 parts of deionized water are added, then transferred into a sealed reactor and the reactor pressure is controlled to 0.9MPa, and then heated to 130°C and kept warm for 5h. After the reaction is completed, it naturally cools to room temperature, and the product is obtained after cyclic washing with methanol and ethanol and drying.
[0065] Comparative Example 5
[0066] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.5 parts of copper sulfate pentahydrate and 0.7 parts of titanium dioxide are mixed and added to 120 parts of DMF solution, and after heating to 70°C, 1.6 parts of succinic anhydride and 0.32 parts of γ-aminopropyltriethoxysilane are added, and stirred at 80rpm for 45min; S2: 1.5 parts of 1,3,5-benzenetricarboxylic acid and 0.7 parts of 1,4-diaminobenzene mixed DMF solution (a total of 80 parts) are added, the temperature is raised to 82°C, and stirred at 80rpm for 90min until uniform, and then the temperature is lowered to 45°C, stirring at 40rpm for 18h; S3: after the reaction is completed, the temperature naturally drops to room temperature, and the mixture is allowed to stand for 5.5h, then centrifuged and filtered, washed with DMF and deionized water three times in sequence, and then vacuum dried until completely dry.
[0067] Comparative Example 6
[0068] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.5 parts of copper sulfate pentahydrate and 0.2 parts of titanium dioxide are mixed and added to 120 parts of DMF solution, and after heating to 70°C, 0.8 parts of succinic anhydride and 0.12 parts of γ-aminopropyltriethoxysilane are added, and stirred at 80rpm for 45min; S2: 2.3 parts of 1,3,5-benzenetricarboxylic acid and 1.4 parts of 1,4-diaminobenzene mixed DMF solution (a total of 80 parts) are added, the temperature is raised to 82°C, and stirred at 80rpm for 90min until uniform, and then the temperature is lowered to 45°C, stirring at 40rpm for 18h; S3: after the reaction is completed, the temperature naturally drops to room temperature, and the mixture is allowed to stand for 5.5h, then centrifuged and filtered, washed with DMF and deionized water three times in sequence, and vacuum dried until completely dry.
[0069] Comparative Example 7
[0070] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 45 nm.
[0071] Performance Evaluation
[0072] Brightness test: The thermoplastic resin coatings prepared in the embodiments and comparative examples were coated on glass as a substrate and cured into coatings, and then brightness tests were performed. The coating thickness was 0.1 mm. The brightness test of the coating was performed using a brightness meter. The test angle was 60°. The measured values were taken as the average of 10 tests and recorded in Table 1.
[0073] Alkali resistance test: The thermoplastic resin coatings prepared in the embodiments and comparative examples were coated on glass as a substrate and cured into coatings, and then an alkali resistance test was performed. The coating thickness was 0.1 mm, and the test solution was a 10 wt % NaOH solution. The prepared samples were completely immersed in the NaOH solution to ensure that the sample surface was completely covered by the solution. The test temperature was 25 ± 2 ° C, and the immersion time was 48 h. After the test, the coating was observed for obvious damage, corrosion, cracking, blistering, and yellowing. If so, it was recorded as unqualified, otherwise it was qualified. 50 groups of samples were tested in each group to obtain the qualified rate of the samples, which was recorded in Table 1.
[0074] Salt spray corrosion resistance test: The thermoplastic resin coatings prepared in the embodiments and comparative examples were coated on glass as a substrate and cured into coatings, and then salt spray corrosion resistance tests were performed. The coating thickness was 0.1 mm, the test solution was 5 wt % NaCl, the test temperature was 35 ± 2 ° C, the test relative humidity was 98 ± 2%, the spray angle was 30 °, the distance between the nozzle and the sample surface was 20 cm, the spray rate was 2.0 ml / 80 cm² h, and the test time was 400 h. After the test, the coating was observed for obvious damage, corrosion, cracking, blistering and yellowing. If so, it was recorded as unqualified, otherwise it was qualified. 50 groups of samples were tested in each group to obtain the qualified rate of the samples, which is recorded in Table 1.
[0075] High temperature and high humidity aging resistance test: The thermoplastic resin coatings prepared in the embodiments and comparative examples were coated on glass as a substrate and cured into coatings, and then subjected to a high temperature and high humidity aging resistance test. The coating thickness was 0.1 mm, and the sample was placed in a constant temperature and humidity chamber at a temperature of 70±3°C and a relative humidity of 78±2% for 3 months. After the test, the coating was observed for obvious damage, corrosion, cracking, blistering, and yellowing. If so, it was recorded as unqualified, otherwise it was qualified. 50 groups of samples were tested in each group to obtain the qualified rate of the samples, which was recorded in Table 1.
[0076] Table 1 Performance test results
[0077]
[0078] According to the examples and comparative examples and the data in Table 1, it can be known that by adopting the special technical solutions in the present application, examples 1 to 3 can obtain excellent waterproof, heat-resistant, alkali-resistant, salt spray corrosion-resistant and other properties. This is the result of the combined effect of the modified epoxy resin and modified filler and other technical solutions in the present application. The corresponding properties obtained make the coating have a very excellent market prospect. However, because comparative examples 1 to 7 do not adopt the special technical solutions, the overall performance of the coatings obtained is significantly worse than that of examples 1 to 3, which further proves that the technical effect of the technical solution adopted in the present application is not an obvious technical effect.
Claims
1. A thermoplastic resin coating, characterized in that: The raw materials are as follows: 20-40 parts of thermoplastic acrylic resin, 10-20 parts of fatty alcohol, 10-15 parts of modified epoxy resin, 40-60 parts of glass frit, 4-8 parts of pigment and filler, 10-20 parts of modified filler, 0.2-0.8 parts of mildewproof agent, 1.5-3 parts of defoaming agent, and 100-200 parts of solvent. The viscosity of the thermoplastic acrylic resin is 5000-10000 mPa·s at 25°C; The fatty alcohol is a combination of hexadecanol and dodecanol; the mass ratio of hexadecanol to dodecanol is 4.5-5:1.2-1.5; Preparation method of modified epoxy resin The following steps are involved: S1: Mix bisphenol A epoxy resin and trimethylolpropane triglycidyl ether and add them to a reaction container, stir at 60-80 rpm for 50-55 min, then add toluene diisocyanate and 2-ethyl-4-methylimidazole in sequence, stir at 80-100 rpm for 20-30 min each time, and replace the air atmosphere with nitrogen to protect the reaction container; S2: First, heat to 70-80°C and keep warm for 3-3.5 h, then heat to 110-115°C and keep warm for 2-2.5 h to obtain a pre-product; S3: Finally, mix the pre-product, glutaric anhydride, maleic anhydride and vinyl triethoxysilane and add deionized water, then transfer to a sealed reactor to control the reactor pressure at 0.8-1 MPa, then heat to 120-140°C, keep warm for 4-5 h, and naturally cool to room temperature after the reaction is completed. The product is obtained by washing with methanol and ethanol in a cycle and drying; The mass ratio of the bisphenol A epoxy resin, trimethylolpropane triglycidyl ether, toluene diisocyanate and 2-ethyl-4-methylimidazole is 11-13: 4-4.5: 1.5-2: 0.05-0.1; The mass ratio of the pre-product, glutaric anhydride, maleic anhydride and vinyl triethoxysilane is 10-12: 1-1.2: 1.4-1.8: 0.2-0.22; Preparation method of the modified filler The following steps are involved: S1: Add copper sulfate pentahydrate and titanium dioxide to a DMF solution, heat to 65-75°C, add succinic anhydride and γ-aminopropyltriethoxysilane, and stir at 60-80rpm for 40-50min; S2: Add a mixed DMF solution of 1,3,5-tricarboxylic acid and 1,4-diaminobenzene, heat to 80-85°C, stir at 60-80rpm for 60-90min until uniform, then cool to 45-50°C, continue stirring at 30-40rpm and keep warm for 16-20h; S3: After the reaction is completed, cool to room temperature naturally, stand for 4-6h, then centrifuge and filter, wash with DMF and deionized water 2-3 times in turn, and vacuum dry until completely dry to obtain; The mass ratio of the copper sulfate pentahydrate, titanium dioxide, succinic anhydride and γ-aminopropyltriethoxysilane is 3.4-3.6:0.6-0.8:1.4-1.8:0.3-0.35; The mass ratio of the copper sulfate pentahydrate, 1,3,5-benzenetricarboxylic acid and 1,4-diaminobenzene is 3.4-3.6:2.2-2.4:1.2-1.4; The average particle size of the titanium dioxide is 10-15 nm.
2. The thermoplastic resin coating according to claim 1, characterized in that: The mass ratio of the thermoplastic acrylic resin, the fatty alcohol and the modified epoxy resin is 25-35:14-18:12-15.
3. The thermoplastic resin coating according to claim 2, characterized in that: The mass ratio of the thermoplastic acrylic resin, the glass frit and the modified filler is 25-35:50-55:13-18.
4. The thermoplastic resin coating according to claim 3, characterized in that: The epoxy equivalent of the bisphenol A epoxy resin is 180-220 g / eq; the viscosity of the bisphenol A epoxy resin is 12000-18000 mPa·s at 25°C.
5. The thermoplastic resin coating according to claim 4, characterized in that: The pigment filler is at least one of iron oxide red, cobalt blue, manganese violet and lead molybdate.
6. The thermoplastic resin coating according to claim 5, characterized in that: The defoaming agent is at least one of organic silicon defoaming agents.
7. The thermoplastic resin coating according to claim 6, characterized in that: The mildew preventer is at least one of isothiazolinone, quaternary ammonium salt, benzimidazole or triazine compounds.
8. A method for preparing a thermoplastic resin coating according to any one of claims 1 to 7, characterized in that: The specific steps include: S1: Mix thermoplastic acrylic resin, fatty alcohol, modified epoxy resin, pigments and modified fillers into the solvent, heat to 60-70°C and stir for 1.5-2h until uniform; S2: Grind the glass frit into fine powder of suitable particle size, mix with mildew inhibitor and defoamer, and then mix in a high-speed mixer at 600-800 rpm for 40-50 minutes, then take out and let stand for vacuum defoaming for 15-20 minutes, and you are done.
9. Use of the thermoplastic resin coating according to any one of claims 1 to 7 in glassware waterproof coatings, glassware decorative coatings, glassware sealing coatings, and glassware antistatic coatings.
